Anaerobic Treatment for Palm Oil Mill Effluent Using Covered In-the Ground Anaerobic Reactor (CIGAR) - Agus Haryanto; Shintawati Shintawati; Udin Hasanudin (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Wastewater from crude palm oil mills contains high organic matter, which potentially produces biogas through anaerobic digestion processes. The design and operation of an anaerobic bioreactor require a good understanding of the reaction kinetic in the bioreactor. This study aimed to evaluate the biogas production from POME and to determine the kinetic parameters of microbial growth and the substrate utilization rates in a CIGAR. An experiment was conducted using a 5-m3 bioreactor with a working volume of 4.4 m3. Wastewater from the Bekri palm oil mill was stored in a 5-m3 tank. After stabilization, the wastewater was loaded into the reactor at a rate of 100 to 250 L/d, corresponding to a COD loading rate of 1.373-3.097 kg·m-3.d-1, and an HRT of 18-44 days. Monod, Contois, Moser, and Shuler kinetic models were evaluated. The results showed that the Shuler model performed best for microbial activities, while the first order reaction model performed best for the substrate utilization kinetic. The maximum specific growth rate (μmax) for the Shuler model was 0.052 d-1 and the saturation constant (Kso) was 0.119. The maximum substrate utilization rate constant (ks) was 2.183 d-1 and biomass yield (Yx/s) 0.024 kg/kg. The maximum average efficiency of anaerobic degradation (34.4%) occurred at a feeding rate of 100 L/d with methane yield of 0.120 Nm3/kg of removed COD. This value is relatively low compared to the maximum potential of 0.350 Nm3/kg CODr.